The TikTok Judgment: Examining Brands’ Crisis Response Through Public Discourses in Social Media - Ekaputri, Sarah Derma; Uritani, Anry Dannya Fahrozi (The Indonesian Journal of Communication Studies, 2025)
This research investigates the public discourse associated with crisis communication strategies utilized by two Indonesian skincare brands, A and D, following allegations concerning the overclaims of product ingredients. By employing a qualitative approach that incorporates Discourse Network Analysis (DNA), this study aims to find and map the emergent narratives and relational dynamics found within dialogues as responses to the official press releases issued by each brand on TikTok. Findings indicate a divergence in strategic response: Brand A engaged in a rebuilding approach using a public apology, while Brand D adopted a denial strategy that provoked further antagonism from critics. These contrasts engendered significantly different public responses related to brand trust, perceived quality, consumer loyalty, and perceived risk of the brands. The investigation emphasizes the critical importance of prompt, empathetic, and transparent communication in the context of digital crisis management, offering valuable insights for brands navigating a reputational dilemma in the contemporary social media landscape.